Natural Radionuclides Determination and Radiological Hazard Assessments in Soil from Tual and Kei Islands, Indonesia - S Syarbaini; K Kusdiana; M. Wiyono; D. Iskandar (PPIKSN-BATAN, 2020)
Natural radionuclides 226Ra, 232Th and 40K in soil are the primary component of the background exposure sources of the population. Study of the external exposure due to gamma-ray radiation of natural radionuclides is important because this may contribute significantly to the total annual individual dose. The purpose of this study is to investigate the natural radionuclides in soils collected from Tual and Kei islands and assess the radiological hazard due to natural radionuclides contents in soil. The soil samples were analyzed for natural radionuclides 226Ra, 232Th and 40K using gamma ray spectrometry. Radiological hazard parameters were estimated from the activity concentration of these radionuclides in order to assess health implication of exposure of the general public. The activity concentrations of 226Ra, 232Th and 40K in soil samples varied from 7.50 Bq kg-1 to 6326 Bq kg-1, 0.99 Bq kg-1 to 157 Bq kg-1, 2.97 kg-1to 98.91 Bq kg-1 with the average value of 2162 Bq kg-1; 69.68 Bq kg-1 and 30.74 Bq kg-1, respectively. The absorbed dose rates due to the presence of 226Ra, 232Th and 40K, in soil samples in the studied area vary between the range of 4.88 nGy h-1 and 3018.80 nGy h-1 with the average value of 1042 nGy h-1. The corresponding outdoor annual effective doses ranged between 0.01 mSv y-1 and 3.70 mSv y-1 with the average value of 1.28 mSv y-1. Radium equivalent activities are calculated to be in the range of 10.42 Bq kg-1 -6553.03 Bq kg-1 with the average value of 2264 Bq kg-1.The external and internal hazard indexes vary from 0.03 to 17.71 with the average value of 6.12 and 0.05 to 34.81 with the average value of 11.96, respectively. All calculated average radiological hazard indices were higher than the limits recommended for individual members of the public.